2018
DOI: 10.5144/0256-4947.2018.326
|View full text |Cite
|
Sign up to set email alerts
|

Expression of androgen receptor in invasive ductal breast carcinomas: a clinicopathological study from Jordan

Abstract: BACKGROUNDThe clinical relevance of androgen receptors (ARs) expressed in breast cancer cells and the suggested prognostic impact has been an area of active research. The prevalence rate of AR expression in breast cancer has never been reported among Jordanian patients.OBJECTIVEDetermine the expression rate of ARs among invasive ductal breast cancer cases of different stages and molecular subtypes. Also, analyze the relationship between AR expression and clinicopathologic and immunohistochemical criteria, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…This corresponds to several studies, of them, Eric et al reported that positive lymph nodes formed 56.6% of all cases [41]. Obeidat et al (2018) from Jordan reported that the positive axillary lymph nodes comprised 64.5% of total cases [19]. Moreover, a study from Turkey recorded that 67.99% of patients had positive lymph nodes whereas 32.1%, had no lymph nodes involvement [42].…”
Section: Luminal Her2 + Triple Negative Missingsupporting
confidence: 83%
See 1 more Smart Citation
“…This corresponds to several studies, of them, Eric et al reported that positive lymph nodes formed 56.6% of all cases [41]. Obeidat et al (2018) from Jordan reported that the positive axillary lymph nodes comprised 64.5% of total cases [19]. Moreover, a study from Turkey recorded that 67.99% of patients had positive lymph nodes whereas 32.1%, had no lymph nodes involvement [42].…”
Section: Luminal Her2 + Triple Negative Missingsupporting
confidence: 83%
“…Also, Halbony et al from Jordan reported that the mean age of 115 BC patients was 56.5±12.0 [18]. Similarly, another study from Jordan found that the mean of age was 50 years with ages ranging between 22-79 years [19]. Conversely, the median age and range of BC women patients in Syria at diagnosis was 47yrs [20].…”
Section: Molecular Subtypementioning
confidence: 96%
“…Breast cancer tumorigenesis is a multi-step process including proliferation, apoptosis, autophagy, invasion, migration, metastasis and drug resistance. According to pathological characteristics, human breast cancer can be divided into non-invasive breast cancer (eg, Paget disease of the breast),5 invasive breast carcinoma of special type (eg, invasive apocrine carcinoma, invasive micropapillary carcinoma),6,7 invasive breast carcinoma of no special type (eg, invasive lobular carcinoma, invasive ductal carcinoma),810 inflammatory breast cancer (IBC) and so on. Among them, invasive breast carcinoma of no special type is the most common type and IBC patients often show a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%